Galaxy Assembly Bias: A Significant Source of Systematic Error in the Galaxy-Halo Relationship - Zentner, Andrew R; Hearin, Andrew P; Frank C van den Bosch (arXiv.org, 2015)
It is common practice for methods that use galaxy clustering to constrain the galaxy-halo relationship, such as the halo occupation distribution (HOD) and/or conditional luminosity function (CLF), to assume that halo mass alone suffices to determine a halo's resident galaxy population. Yet, the clustering strength of cold dark matter halos depends upon halo properties in addition to mass, such as formation time, an effect referred to as assembly bias. If galaxy characteristics are correlated with any of these auxiliary halo properties, the basic assumption of HOD/CLF methods is violated. We estimate the potential for assembly bias to induce systematic errors in inferred halo occupation statistics. We use halo abundance matching and age matching to construct fiducial mock galaxy catalogs that exhibit assembly bias as well as additional mock catalogs with identical HODs, but with assembly bias removed. We fit a parameterized HOD to the projected two-point clustering of mock galaxies in each catalog to assess the systematic errors induced by reasonable levels of assembly bias. In the absence of assembly bias, the inferred HODs generally describe the true underlying HODs well, validating the basic methodology. However, in all of the cases with assembly bias, the inferred HODs have systematic errors that are statistically significant. In most cases, these systematic errors cannot be identified using void statistics as auxiliary observables. We conclude that the galaxy-halo relationship inferred from galaxy clustering should be subject to a non-negligible systematic error induced by assembly bias. Our work suggests that efforts to model and/or constrain assembly bias should be high priorities as it is a threatening source of systematic error in galaxy evolution studies as well as the precision cosmology program.